Comparison of the effects of pectoralis muscles stretching exercise and scapular retraction strengthening exercise on forward shoulder - Yoo, Won-gyu (J Phys Ther Sci, 2018)
[Purpose] The purpose of this study was to compare effect in a group of stretching and a group of muscle strengthening exercise for patients with forward scapular posture. [Subjects and Methods] This study was performed in 20 subjects who defined to the forward shoulder posture. The subjects were divided into a group of pectoralis muscles stretching and a group of muscle strength exercise for scapular retraction. [Results] The forward shoulder posture of the group of the scapular retraction exercise was significantly decreased when compared to that of the group of the pectoralis muscles stretching. [Conclusion] It is expected that therapeutic effect can be improved and the period can be shortened when strength exercise for forward shoulder posture is applied as a therapeutic intervention.